Global Grassland Mapping & Monitoring - Sloat, Lindsey L. (World Resources Institute, 2025)
A presentation on Global Pasture Watch Consortium as part of an experience sharing webinar with the Agricultural Transformation Institute, who are developing a national rangeland monitoring system for Ethiopia.